Letter to the Editor. Re: "Acute pancreatitis as the first manifestation of duodenal MALT lymphoma" by Ivona Simkova et al. Biomed Pap Med Fac Univ Palacky Olomouc Czech Repub 2015;159(4):688-94. doi: 10.5507/bp.2015.047 - Vitorino Modesto dos Santos (Biomedical Papers, 2016)
Letter to the Editor.